2020
DOI: 10.1105/tpc.19.00828
|View full text |Cite
|
Sign up to set email alerts
|

The Moss Physcomitrium (Physcomitrella) patens: A Model Organism for Non-Seed Plants

Abstract: Since the discovery two decades ago that transgenes are efficiently integrated into the genome of Physcomitrella patens by homologous recombination, this moss has been a premier model system to study evolutionary developmental biology (evo-devo) questions, stem cell reprogramming, and the biology of non-vascular plants. P. patens was the first non-seed plant to have its genome sequenced. With this level of genomic information together with increasing molecular genetic tools, a large number of reverse genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
183
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 143 publications
0
183
0
1
Order By: Relevance
“…Much of what is detected as heterozygous is probably due to very closely related (identical and near-identical) paralogs that are known to be present in the P. patens genome (Rensing et al, 2008). Yet, the low apparent Wi heterozygosity reinforces that P. patens is a predominantly selfing species (Perroud et al, 2019;Meyberg et al, 2020;Rensing et al, 2020).…”
Section: Natural Population Variation and Selectionmentioning
confidence: 96%
See 1 more Smart Citation
“…Much of what is detected as heterozygous is probably due to very closely related (identical and near-identical) paralogs that are known to be present in the P. patens genome (Rensing et al, 2008). Yet, the low apparent Wi heterozygosity reinforces that P. patens is a predominantly selfing species (Perroud et al, 2019;Meyberg et al, 2020;Rensing et al, 2020).…”
Section: Natural Population Variation and Selectionmentioning
confidence: 96%
“…For the moss model Physcomitrium patens (Hedw.) Mitten (previously known as Physcomitrella patens) (Beike et al, 2014;Medina et al, 2019;Rensing et al, 2020) whole genome SNP sets between the reference genome accession, Gransden (Gd) (Rensing et al, 2008;Lang et al, 2018), and the accessions Villersexel (Vx) (Kamisugi et al, 2008), Reute (Re) (Hiss et al, 2017) and Kaskaskia (Ka) (Perroud et al, 2011) have been reported (Hiss et al, 2017). Specifically, the genetic difference between Gd and Vx has been used to generate the first sequence-anchored genetic linkage map (Kamisugi et al, 2008) and recently the P. patens chromosome level genome assembly (Lang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in mosses and hornworts has begun to dissect the relatively simpler mechanisms of stomatal development in bryophyte species (Merced and Renzaglia, 2013Pressel et al, 2014). Like other mosses, the model species P. patens (Rensing et al, 2020) employs a simple form of stomatal development ( Figure 1B) and a number of genes orthologous to those of Arabidopsis have been shown to regulate stomatal development and patterning (MacAlister and Bergmann, 2011;Caine et al, 2016;Chater et al, 2016). Surprisingly, despite the elucidation of genetic regulators, our understanding of stomatal and epidermal ontogeny in this model moss remains limited ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we generated a conditional myosin XI allele through rational mutagenesis. We used the plant P. patens, which is a great model to study polarized growth due to its simple cytology and tractable genetics (Reski, 2018;Rensing et al, 2020). Our results prove that myosin XI clusters secretory vesicles at the cell's apex and that myosin XI is essential for persistent apical growth.…”
Section: Introductionmentioning
confidence: 73%